Updates on the little-known Firminus maltensis, with revisited classification based on the anatomy of everted endophallus (Coleoptera: Scarabaeidae, Melolonthinae) - Uliana, Marco; Gallerati, Valerio (Fragmenta entomologica, 2022)
New information on the almost unknown rhizotrogine Firminus maltensis Rössner & Zorn, 2013, endemic to the Maltese Archipelago, is provided, based on new specimens recently collected. The species is transferred to the genus Rhizotrogus, introducing Rhizotrogus maltensis (Rössner & Zorn, 2013) as comb. nov., based on new evidence provided by the morphology of the endophallus, whose everted structure is addressed for the first time in the genera Firminus and Rhizotrogus. A comparative diagnostic characterization for the endophalli of the two genera is proposed. Some morphological traits are also discussed, and the first behavioural and ecological observations are provided.